The Influence of Addressee Gender on Spoken Fluency among EFL Learners - Hammad Ur Rahman; Jebran Khan; Ruba Urooj; Rukhsana Ahmad (Development in Language Studies, 2025)
This research investigates the impact of addressee gender on the spoken fluency of English as a Foreign Language (EFL) learners. The study examines how interactions in same-gender and mixed-gender contexts affect three key aspects of fluency: Automaticity, lexical density, and lexical diversity. A sample of 10 intermediate-level Pashto-speaking students (5 males and 5 females) was selected for the study. Data was collected through audio recordings of spoken corpora in four different contexts: female-female, female vs. mixed gender, male-male, and male vs. mixed gender interactions. The findings reveal significant differences in fluency based on the gender composition of the interaction. Female participants demonstrated higher automaticity and lexical density in same-gender interactions, while male participants exhibited greater fluency, lexical density, and diversity in mixed-gender contexts. These results suggest that the gender of the addressee influences not only the speed and content richness of speech but also the variety of vocabulary used. The study underscores the importance of considering gender dynamics in EFL teaching and offers recommendations for educators to enhance fluency through gender-aware pedagogical strategies. Further research is suggested to explore the impact of addressee gender on other language skills and in various communication settings.